Corporate social responsibility strategy: strategic options, global considerations - Galbreath, Jeremy (Emerald Group Publishing Ltd, 2006)
Purpose: To further the dialogue on corporate strategy and corporate social responsibility (CSR). Specifically, to describe four options with respect to CSR strategies and to offer points of consideration for moving home country CSR strategies to host countries.Design/methodology/approach: The approach is based on developing a conceptualization of various CSR strategic options. The paper also incorporates key global considerations for moving home country CSR strategies to host country operations.Findings: The analysis suggests that CSR can not be separated from corporate strategy. Thus, firms have several factors to consider with respect to choosing appropriate CSR strategies. Not only are there fundamental strategic goals and outcomes to consider, but also a variety of cross-border factors that can potentially complicate the success of CSR strategies if not examined appropriately.